Mathematical Literacy-Oriented Student Worksheets Using the Sidoarjo Context - Mohammad Faizal Amir; Ainiya Rahma Septiarini; Mahardika Darmawan Kusuma Wardana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2023)
This study aims to produce student worksheets (SW) oriented toward mathematical literacy using the Sidoarjo context that is valid, practical, effective has potential effects to improve the mathematical literacy of elementary school students. This type of study is a design research type of development study. The subjects of this study were students of grade IV A Kepunten State Elementary School for the academic year 2021/2022 totaling 25 students. Data collection techniques are walkthrough, observation, test, and interview. Sampling technique using purposive sampling with descriptive analysis. The results of the SW mathematical literacy using the Sidoarjo context on the area and circumference of a valid flat shape material based on content, construct, and language after going through the development stage in the form of expert review and one-to-one. The practicality of SW is seen in the small group development stage. The effectiveness developed SW has a potential effect on students' mathematical literacy skills. This shows that mathematical literacy-oriented SW using the Sidoarjo context can be used in area and circumference learning. This study implies that it can fill the gap between mathematical literacy problems and the need for alternative teaching materials in the form of SW that involves a cultural context. Hence, teaching materials are available that can facilitate mathematical literacy construction as well as understanding that is easier to understand by elementary students, especially in learning areas and circumferences in the Sidoarjo region.